Ethnic differences in singleton preterm birth in England and Wales, 2006‐12: Analysis of national routinely collected data. Issue 6 (22nd October 2019) - Li, Yangmei; Quigley, Maria A.; Macfarlane, Alison; Jayaweera, Hiranthi; Kurinczuk, Jennifer J.; Hollowell, Jennifer
Abstract: Background: Data recorded at birth and death registration in England and Wales have been routinely linked with data recorded at birth notification since 2006. These provide scope for detailed analyses on ethnic differences in preterm birth (PTB). Objectives: We aimed to investigate ethnic differences in PTB and degree of prematurity in England and Wales, taking into account maternal sociodemographic characteristics and to further explore the contribution of mother's country of birth to these ethnic differences in PTB. Methods: We analysed PTB and degree of prematurity by ethnic group, using routinely collected and linked data for all singleton live births in England and Wales, 2006‐2012. Logistic regression was used to adjust for mother's age, marital status/registration type, area deprivation and mother's country of birth. Results: In the 4 634 932 births analysed, all minority ethnic groups except 'Other White' had significantly higher odds of PTB compared with White British babies (ORs between 1.04‐1.25); highest odds were in Black Caribbean, Indian, Bangladeshi and Pakistani groups. Ethnic differences in PTB tended to be greater at earlier gestational ages. In all ethnic groups, odds of PTB were lower for babies whose mothers were born outside the UK. Conclusions: In England and Wales, Black Caribbean, Indian, Bangladeshi, Pakistani and Black African babies all have significantly increased odds of being born preterm compared with White British babies. Bangladeshis apart, these groups are particularly at risk of extremely PTB. In all ethnic groups, the odds of PTB are lower for babies whose mothers were born outside the UK. These ethnic differences do not appear to be wholly explained by area deprivation or other sociodemographic characteristics.